Textiles and clothing sustainability : nanotextiles and sustainability - Muthu, Subramanian Senthilkannan (Springer, 2016)
This book highlights the sustainability aspects of textiles and clothing sector in light of nanomaterials and technologies. The invasion of nano in every industrial sector has been important and has made remarkable changes as well as posed new challenges, including the textiles and clothing sector. There is quite a great deal of research happening in terms of nano materials for textiles across the globe, some of which are covered in this book. .
Keywords: Textile fabrics -- Environmental aspects.; Textile fibers -- Environmental aspects.; Nanofibers.; elektronické knihy; electronic books